An international survey of the nutrition management of chylothorax: a time for change. (15th August 2019) - Marino, L. V.; Bell, K. L.; Woodgate, J.; Doolan, A.
Abstract: Introduction: Although chylothorax is an uncommon complication following paediatric cardiothoracic surgery, it has significant associated morbidities and increased in-hospital mortality, as well as results in higher costs. A lack of prospective evidence or consensus guidelines for management of chylothorax further hinders optimal management. The aim of this survey was to characterise variations in practice in the management of chylothorax and to identify areas for future research. Materials and methods: A descriptive, observational survey investigating conservative management practices of chylothorax was distributed internationally to health-care professionals in paediatric intensive care and cardiology units. The survey investigated five domains: the first providing general information about health-care professionals and four domains focusing on clinical practice including diet composition and duration. Results: In total, sixty-four health-care professionals completed the survey, representing 38 organisations from 16 countries. The respondents were dietitians (80%), physicians (19%), and nurses (1%). In Australia and New Zealand, management was most commonly directed by physicians' preference (67%) as compared to unit protocols in Europe (67%), United States of America (67%), and Other regions (55%). Dietitians in Australia/New Zealand, United Kingdom, and Ireland followed the most restrictive diet therapy recommending <5 g long chain triglyceride fat per day (p < 0.00001). The duration of diet therapy significantly varied between regions: Australia/New Zealand: 4 weeks (36%) and 6 weeks (43%); Europe: 4 weeks (25%) and 6 weeks (57%); and North America: 4 weeks (18%) and 6 weeks (75%) (p < 0.00001). Conclusions: This survey highlights international variations in practice in the management of chylothorax, particularly with respect to treatment duration and dietary fat restriction. Future research should include a multi-centre randomised controlled trial to inform evidence-based practice and reduce morbidity, particularly poor growth.